Peran Mediasi Job Embeddedness Terhadap Innovative Work Behavior - Nuzulul Hidayah; Retno Dwiyanti; Mohd Nazri Abdul Rahman; Mahdi Anbari; Endah Silawati (LPPM Universitas Abdurrab, 2026)
Innovative work behavior is essential for enhancing organizational competitiveness; however, studies examining its psychological mechanisms among millennial female employees remain limited. This study aims to analyze the effects of psychological contract fulfillment and psychological empowerment on innovative work behavior, with job embeddedness as a mediating variable. A quantitative survey was conducted with 385 millennial female employees aged 25–43 years working in the private sector in Indonesia, selected using convenience sampling. Data were collected through standardized questionnaires and analyzed using PLS-SEM with SmartPLS 4. The results indicate that psychological contract fulfillment and psychological empowerment have positive and significant effects on job embeddedness and innovative work behavior. Moreover, job embeddedness partially mediates the relationship between the two psychological variables and innovative work behavior. These findings emphasize the importance of strengthening psychological resources and job embeddedness to promote innovative work Behavior among millennial female employees.